Rhinovirus: A Narrative Review on Its Genetic Characteristics, Pediatric Clinical Presentations, and Pathogenesis - Bizot, Etienne; Bousquet, Anais; Charpié, Maelle; Coquelin, Florence; Lefevre, Servane; Le Lorier, Justin; Patin, Margaux; Sée, Perrine; Sarfati, Eytan; Walle, Servane; Visseaux, Benoit; Basmaci, Romain (Frontiers in Pediatrics, 2021)
Human Rhinoviruses (HRVs) are the leading cause of common colds. With the development of new molecular methods since the 2000s HRVs have been increasingly involved among severe clinical infections. Recent knowledge of the HRV genetic characteristics has also improved the understanding of their pathogenesis. This narrative review aims to provide a current comprehensive knowledge about this virus in pediatric community. HRVs represent a main cause of upper and lower respiratory tract infections in children. HRV is the second virus involved in bronchiolitis and pneumonia in children and HRV bronchiolitis has a higher risk of recurrent wheezing episode or asthma. Some recent findings described HRVs in stools, blood or cerebrospinal fluid thanks to new molecular techniques such as polymerase chain reaction (PCR) by detecting HRVs with high sensibility. However, the high rate of asymptomatic carriage and the prolonged excretion in post-symptomatic patients complicate interpretation. No sufficient data exist to avoid antibiotic therapy in pediatric high-risk population with HRV detection. Severe clinical presentations due to HRVs can be more frequent in specific population with chronic pathology or genetic particularity. Inflammatory response is mediated by NF-kappa B pathway and production of IFN-beta and -gamma, IL8, and IL1b. No specific treatment or antiviral therapy exists, although research is still ongoing. Nowadays, in addition to benign diseases, HRVs is recognized to be involved in some severe clinical presentations. Recent advances in genetic knowledge or specific inflammatory response may lead to specific treatment.